Pengaruh Bentuk Umpan Balik dan Gaya Kognitif terhadap Hasil Belajara Trigonometri - Chatarina Febriyanti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
Purpose of this research is to find and analyze empirically trigonometry learning outcomes in terms of the form of feedback and cognitive style. The research design used in this study is a 2 x 2 factorial design with three variables consisting of two independent variables, namely the form of feedback and cognitive styles, as well as the dependent variable, which is the result of learning trigonometry. The data collection was done by using the test (variable learning outcomes trigonometry), questionnaire technique (variable cognitive style) and documentation techniques (variable feedback form). The collected data were then analyzed using the technique of two-way ANOVA followed by t-test due to the influence of the form of feedback with cognitive style on learning outcomes trigonometry. Before the data were analyzed, first performed descriptive statistical analysis and test data requirements (test for normality and homogeneity test). The results showed that: (1) There is the influence of feedback on learning outcomes trigonometry, (2) There is the influence of cognitive style on learning hasill trigonometry, (3) There is a shape Interaction Effects of feedback and cognitive style on learning outcomes trigonometry.